Stop the bleed campaign: A qualitative study from our experience from the middle east - AlSabah, Salman (Ann Med Surg (Lond), 2018)
BACKGROUND: Bleeding due to unintentional injuries are a leading cause of death in the younger population. The immediate involvement of lay bystanders has been proven to be imperative in outcomes, however, there still is less than 30% of out-of-hospital resuscitation attempts initiated by them. STUDY DESIGN: The Stop the Bleed campaign was initiated in Kuwait in September-2017, with the aim to raise awareness and train the general public on emergency situations. A survey questionnaire was distributed to a sample of 150 participants to assess their comprehension. RESULTS: A total of 1531 participants were trained by the campaign. More than half of the participants have had no previous training of any sort for emergency situations, with the majority (86%) of those queered expressing desire to learn about how to deal with trauma and bleeding cases. After training, most participants were able to demonstrate knowledge of how to deal with unstoppable bleeding, know where and when to place a tourniquet, knew how to respond to epistaxis, and the ability to recognize signs of internal bleeding, with 89% expressing that the ‘Stop the Bleed’ campaign was useful for promoting health and raising awareness on safety of individuals. CONCLUSION: With the appropriate first-aid training and skill retention, lay members of the public can potentially contribute to a positive and important post-trauma medical response.